Metastatic cancers promote cachexia through ZIP14 upregulation in skeletal muscle. (June 2018) - Wang, Gang; Biswas, Anup; Ma, Wanchao; Kandpal, Manoj; Coker, Courtney; Grandgenett, Paul; Hollingsworth, Michael; Jain, Rinku; Tanji, Kurenai; Lόpez-Pintado, Sara; Borczuk, Alain; Hebert, Doreen; et al.
Abstract Patients with metastatic cancer experience a severe loss of skeletal muscle mass and function known as cachexia. Cachexia is associated with poor prognosis and accelerated death in patients with cancer, yet its underlying mechanisms remain poorly understood. Here, we identify the metal-ion transporter ZRT- and IRT-like protein 14 (ZIP14) as a critical mediator of cancer-induced cachexia. ZIP14 is upregulated in cachectic muscles of mice and in patients with metastatic cancer and can be induced by TNF-α and TGF-β cytokines. Strikingly, germline ablation or muscle-specific depletion ofZip14 markedly reduces muscle atrophy in metastatic cancer models. We find that ZIP14-mediated zinc uptake in muscle progenitor cells represses the expression ofMyoD andMef2c and blocks muscle-cell differentiation. Importantly, ZIP14-mediated zinc accumulation in differentiated muscle cells induces myosin heavy chain loss. These results highlight a previously unrecognized role for altered zinc homeostasis in metastatic cancer–induced muscle wasting and implicate ZIP14 as a therapeutic target for its treatment. Accumulation of zinc in muscle cells resulting from transcriptional upregulation of metal transporter ZIP14 causes muscle atrophy and promotes cachexia in metastatic cancer.